Manajemen Pendidikan Pesantren Dalam Upaya Meningkatkan Mutu Santri Di Pondok Pesantren Darus Sa’adah Lampung Tengah - Majid, Lukman Abdul (DIMAR: Jurnal Pendidikan Islam, 2023)
The Darussa’adah Mojoagung Seputih Jaya Islamic Boarding School, established since 1986, plays a significant role in the development of Islamic religious education, particularly in the Seputih Jaya community and more broadly in the Gunung Sugih and Lampung Tengah regions. The management of the boarding school plays a key role in enhancing the quality of education at the Darus Sa’adah Boarding School in Lampung Tengah by employing various strategies, including: Firstly, the boarding school management actively contributes to improving the quality of education at Darus Sa’adah Boarding School, as evidenced by the effective and efficient implementation of inputs that yield positive outputs through a quality educational process. The boarding school successfully produces graduates who are not only proficient in religious studies but also skilled in various other fields. Furthermore, the educational legitimacy of the boarding school has been recognized by the government. Secondly, to enhance the quality of education, Darus Sa’adah Boarding School has devised various programs, including daily, weekly, monthly, and even annual programs, organized and implemented by the boarding school administrators and all students. These programs are supported by effective and efficient madrasah education, as well as an environment and facilities that are adequate.